2020
DOI: 10.3389/fpsyt.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Outpatient Variables That May Help to Prevent Further Detention

Abstract: Background: Forensic outpatient treatment in Germany helps forensic patients back into society while managing the risk that these individuals present to public safety. Measures used to achieve this objective include ongoing psychiatric treatment and monitoring, case management, and controlling risk factors that may cause criminal behavior. In addition to the effects of treatment and control, good living conditions have been hypothesized to help prevent criminal recidivism and a number of studies have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There is an urgent and ongoing need to develop and improve effectiveness of evidence-based interventions for forensic psychiatric patients ( 10–13 ). A supportive social network is considered an important protective factor that may improve mental health outcomes and reduce criminal recidivism in forensic psychiatric care ( 14–16 ). Yet, the effectiveness of interventions aimed at promoting supportive social networks among forensic psychiatric patients has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent and ongoing need to develop and improve effectiveness of evidence-based interventions for forensic psychiatric patients ( 10–13 ). A supportive social network is considered an important protective factor that may improve mental health outcomes and reduce criminal recidivism in forensic psychiatric care ( 14–16 ). Yet, the effectiveness of interventions aimed at promoting supportive social networks among forensic psychiatric patients has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A supportive social network is considered an important protective factor against mental health problems and criminal recidivism ( 14–18 ). Multiple cross-sectional studies found that social support is positively related to mental health (recovery) and mental wellbeing in general and psychiatric populations ( 19–22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of unit data in provisional discharge decisions and outcome is made clear by the present findings. Specifically, individuals who successfully traversed the hospital level systems are more likely to both be discharged and successful on such discharge (Klinger et al, 2020) and that includes the ability to work with a treatment team and establish mutual goals relevant to discharge planning (McDonnaugh et al, 2020). Transitions to lower security levels are associated with stability and greater focus on preparedness for community reintegration.…”
Section: Forensic Hospital Data and Provisional Dischargementioning
confidence: 99%
“…Simultaneously, a supportive social network consisting of individuals with criminal attitudes and behaviors is related to an increased risk of criminal recidivism [ 11 , 12 ]. Furthermore, previous research has extensively established positive effects of social support on other relevant treatment outcomes, such as mental health recovery, wellbeing, and quality of life in (forensic) psychiatric populations [ 8 , 13 15 ]. Therefore, interventions targeting social network enhancement in the community are potentially important in improving treatment outcomes of forensic psychiatric outpatients with limited supportive social networks.…”
Section: Introductionmentioning
confidence: 99%